Strategic fixed income investing : an insider's perspective on bond markets, analysis, and portfolio management - Simko, Sean P., 1970- (Wiley finance series, 2013)
A fixed income portfolio that will weather volatility and instability/b Designing a fixed income portfolio is an essential skill of any investment manager or advisor. This book outlines the critical components to successfully navigate through stable and turbulent markets, using real-life lessons from a seasoned institutional asset manager. The first section includes commentary on the changing fixed income market and overall economy, while the second section outlines the processes to navigate these ever-evolving markets including portfolio construction, the Federal Reserve, credit analysis and trade execution. Ladder Methodology is highlighted and the book discusses its pros and cons, gives examples of both well-constructed and poorly executed laddered bond portfolios and offers alternatives to traditional asset classes.ulliBenefit from lessons learned, providing real life examples of market scenarios and trades/liliPrepare fixed income portfolios that can weather any storm/liliWritten by Sean P. Simko, an expert on fixed income investing, who shares his investing experiences from the past 16 years/liliOutlines the key principles of the Ladder strategy/li/ul From strategy to execution, iStrategic Fixed Income Investing/i offers the road map to help investment managers prepare portfolios that will insulate investments against adverse market conditions.